2008
DOI: 10.1002/app.28542
|View full text |Cite
|
Sign up to set email alerts
|

Mesomorphic phases of main‐chain liquid‐crystalline polymers with pendent sulfonic acid groups

Abstract: Some main-chain liquid-crystalline polymers were synthesized with pendent sulfonic acid groups (0-6 wt %) on the polymer backbone. The solution viscosity behavior, the chemical structures, and the liquid-crystalline (LC) properties were characterized with Fourier transform infrared spectroscopy, elemental analysis, 1 H-NMR, differential scanning calorimetry, polarizing optical microscopy, and X-ray measurements. All the polymers displayed a smectic mesophase with a mesogenic range of 142-1558C and good thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although several research groups reported on the synthesis and characterization of sulfonated LCPs,31–41 their application in the preparation of LCP/CNT nanocomposites is rather limited,42 and LCP/ND nanocomposites have not been reported at all. Zhang and coworkers explored different methods to prepare main‐chain LCPs with pendant sulfonate groups.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several research groups reported on the synthesis and characterization of sulfonated LCPs,31–41 their application in the preparation of LCP/CNT nanocomposites is rather limited,42 and LCP/ND nanocomposites have not been reported at all. Zhang and coworkers explored different methods to prepare main‐chain LCPs with pendant sulfonate groups.…”
Section: Introductionmentioning
confidence: 99%
“…In an extensive series of studies, they used dye molecules like Brilliant Yellow31–34 and Fast Yellow35 as the sulfonate‐containing monomer to prepare LCPs via interfacial polymerization. They also report on the synthesis of liquid crystalline polyesters (LCPEs) via a three‐step synthetic route that makes use of Brilliant Yellow36 and 2‐hydroxy‐5‐carboxy‐benzenesulfonic acid derivatives as one of the monomers 37, 38. Finally, dimethyl 5‐sodiosulfoisophthalate39 and sulfoterephthalic acid40 have been used in melt condensation reactions and very recently the post‐treatment (sulfonation) of an LCP was demonstrated 41.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, due to the stringent environmental standards and economic pressures, much attention has been directed toward to immobilized sulfuric acid on solid support to reducing of waste, effective separation of catalyst and simple purification of the products. Toward this aim, many support materials such as polymers, amorphous and mesoporous carbon, mesoporous silica and amorphous silica are often used for immobilization of sulfuric acid, which can be separated by conventional separation techniques such as centrifugation and filtration.…”
Section: Introductionmentioning
confidence: 99%